Fertility Intention Among Chinese Reproductive Couples During the COVID-19 Outbreak: A Cross-Sectional Study - Chu, Kun; Zhu, Ronghui; Zhang, Yi; Pang, Wenjuan; Feng, Xu; Wang, Xiang; Wu, Cheng; Sun, Ningxia; Li, Wen (Frontiers in Public Health, 2022)
Decline in fertility rate has been observed worldwide, which hampers social development severely. Given the impacts of COVID-19 on individuals and the society, it’s of great significance to investigate the fertility intention of reproductive couples under COVID-19. The convenience sampling method was used to obtain study sample. Self-administered questionnaire included the following components: sociodemographic characteristics (age, residence, education, occupation, characteristics of the couples, annual household income), reproductive history (parity, number of children, child gender, duration of preparing pregnancy), and attitudes towards COVID-19, was distributed online via applet of WeChat. The results showed that among 4133 valid questionnaires, 1091 had the fertility intention before COVID-19, whereas 3042 did not, indicating a fertility intention rate of 26.4% among the participated couples. Of the 1091 couples who had fertility intention before COVID-19, 520 (47.7%) were affected by the outbreak, whereas 571 (52.3%) were not. By multivariable logistic regression analysis, we further found that couples living in Hubei Province, the epicenter in China (OR 2.20, 95% CI 1.35-3.60), and couples who prepared pregnancy longer before COVID-19 (OR 1.19, 95% CI 1.06-1.33) were more likely to change their fertility intention under the pandemic. In addition, most of the participants reported their fertility intention was affected by the inconvenience of seeking medical service under COVID-19. Therefore, more forms of medical services in order to provide convenience for the patients might be effective ways to reverse the declined fertility intention rate in facing COVID-19.